Evaluation of quality of mozzarella cheese (Bangladesh Veterinarian, 2010)
The physical and chemical qualities of mozzarella cheese prepared from cow andbuffalo milk were evaluated by a panel of judges (flavour and taste, body and texture,finish and colour) and by chemical tests (acidity, pH, fat, protein, lactose and ash). Theflavour and taste, finish and colour of cow cheese were not significantly different fromthose of buffalo cheese. Fat, protein, lactose and ash content of cow cheese weresignificantly higher than those of buffalo cheese. (Bangl. vet. 2010. Vol. 27, No. 1, 36 – 42)DOI: 10.3329/bvet.v27i1.5913